2015
DOI: 10.1016/j.ejvs.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable Velcro® Compression Devices are More Effective than Inelastic Bandages in Reducing Venous Edema in the Initial Treatment Phase: A Randomized Controlled Trial

Abstract: Re-adjustable AVCDs with a resting pressure of around 40 mmHg are more effective in reducing chronic venous edema than IBs with a resting pressure of around 60 mmHg. AVCDs are effective and well tolerated, not only during maintenance therapy, but also in the initial decongestive treatment phase of patients with venous leg edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 17 publications
2
49
0
17
Order By: Relevance
“…The sum of scores was calculated to provide a comfort index and an index of other parameters. 22 The researchers reported that mean interface pressures were higher in the bandaging group than the AVCD group at supine and standing at application; however, at Time 1 (24 hours) this was reversed. Mean volume reduction at Time 1 and 7 was significantly higher in the AVCD group than the bandaging group (p>.001).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The sum of scores was calculated to provide a comfort index and an index of other parameters. 22 The researchers reported that mean interface pressures were higher in the bandaging group than the AVCD group at supine and standing at application; however, at Time 1 (24 hours) this was reversed. Mean volume reduction at Time 1 and 7 was significantly higher in the AVCD group than the bandaging group (p>.001).…”
mentioning
confidence: 99%
“…However, outcomes were limited to a 24 hour period, and details of clinical effectiveness or patient comfort over a longer period were not reported. 21 In the second research paper, Mosti et al 22 compared the efficacy and comfort of inelastic bandaging (IB) and an Adjustable Velcro Compression Device (AVCD) in 36 patients (40 legs) with untreated venous oedema due to superficial or deep venous insufficiency. Patients had a mean age of 71.4 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This fact also explains the more pronounced edema reduction of Velcro-devices versus inelastic bandages in lymphedema patients. 17 Only few studies are available up to now concerning the clinical efficacy of Velcro systems. 18 The presented study should show that self-management using such devices is feasible and promising.…”
Section: Discussionmentioning
confidence: 99%
“…4b). If a patient is still able to put on his/her shoes independently, he/she can be considered for independent handling of the materials of adaptive compression therapy (34). It has been shown that patients can sometimes already manage these systems independently after only a short introduction (35).…”
Section: New Developmentsmentioning
confidence: 99%